Initial response of Orthoptera to beaver (Castor fiber) reintroductions in post-arable enclosures - Tim Gardiner; Emily Crisp (Journal of Orthoptera Research, 2025)
Rewilding aims to restore ‘self-willed’ ecosystems involving the creation of habitat subject to stochastic disturbance, connected by favorable corridors for dispersal of animals including insects. Herbivores such as the Eurasian beaver Castor fiber (Linnaeus, 1758) have been reintroduced in the UK to promote natural flood management as part of a rewilding strategy. At Spains Hall in Finchingfield (south-east England), beavers were released into two large enclosures (both c. 20 ha) in March 2023 which were concurrently reverting from arable farmland to riparian meadow. Monitoring of Orthoptera 15–18 months after release in June-September 2024 revealed statistical evidence that the abundance of the two localised groundhoppers, Tetrix subulata (Linnaeus, 1758) and Tetrix undulata (Sowerby, 1806), and the lesser marsh grasshopper Chorthippus albomarginatus (De Geer, 1773), was higher in the beaver enclosure meadows than in the control plots. The Essex Red Data List species, the common green grasshopper Omocestus viridulus (Linnaeus, 1758), was also recorded within the beaver meadows. The damming of the watercourse in one enclosure led to the creation of new off-line lotic channels and wet ground which were important for these species, particularly bare mud margins which were used by groundhoppers (Tetrigidae). There was also evidence that meadows on the east side of the river had a greater abundance of long-winged conehead Conocephalus fuscus (Fabricius, 1793) and T. subulata than the west, perhaps due to the sheltered microclimate and wetland features on this side of the channel, particularly in the beaver enclosures. We conclude that in enclosures on former arable farmland Orthoptera may respond to damming which quickly creates beaver meadows in flooded areas within the first two years of release. However, only one enclosure had dams in this study so the effects of beavers may be dependent on variables such as habitat quality and watercourse characteristics.